O Índice de Desenvolvimento Familiar – IDF – para fins de avaliação e acompanhamento de famílias beneficiárias de Programas de Transferência Condicionada de Renda: focalizando os programas Bolsa Família e Vida Nova no município de Nova Lima – MG - Aguiar, Fátima Monteiro de (2010)
This research was developed from the investigation of the potentialities and limitations of the Family Development Index (IDF) as a multidimensional indicator of poverty in the monitoring of beneficiary families of the Conditional Income Transfer Program (PTCR), in the subsidy to decision-making of governors, managers and technicians in relation to the adoption and implementation of public, social and urban areas policies promoting social justice, and supporting families to achieve better levels of family development. Our goal was to analyze the potentialities of that index as a tool to track the inclusion and withdrawing of families to receive the benefits from the PTCR. The index was applied to a group of beneficiary families of the Vida Nova Program (New Life Program) – municipal program of income transfer with conditionalities – of the Municipality of Nova Lima, State of Minas Gerais, co-financed with the Bolsa Família Program (Family Allowance Program). The approaches to poverty were also analyzed, emphasizing the multidimensionality of the phenomenon, and, in a practical perspective, the quantitative results, which were obtained from the families’ permanence in the Program in a period of two years, gauging the synthetic IDF and its dimensions, were identified. This research also shows the conception and the design of the Vida Nova Program, which aggregates the income transfer to other dimensions and innovates in using the IDF in its administration, seeking to contribute to the advancement of methodologies and tools of family monitoring. This paper is organized into five parts. The first one addresses the one-dimensional and multidimensional conceptions of poverty. The second one contextualizes the PTCRs in the social protection system in Brazil, emphasizing the importance of these programs to achieve better levels of social welfare, besides describing the Bolsa Família Program: the Brazilian PTCR. The third part presents the IDF as a multidimensional indicator and management tool, describing the conceptions, objectives and dimensions which compose it, as well as its potentialities and limitations. The fourth part presents the Vida Nova Program: the PTCR of the Municipality of Nova Lima, its format, the legal bases, the focus, the socioeconomic reality of the municipality and the specificities of this Program. The fifth part discusses and presents the implementation of the IDF for the monitoring of the families, analyzing its appropriateness and relevance as a tool to report the degree of development of the beneficiary families of the PTCRs.